1973
DOI: 10.1083/jcb.58.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of Ethidium Bromide Resistance in Simian Virus 40-Transformed Hamster Cells

Abstract: This study describes the isolation and subsequent characterization of four mammalian cell lines resistant to ethidium bromide (EB) . Treatment of the simian virus 40-(SV40) transformed hamster cell line F5-1 first led to the establishment of the F2 cell line, which is resistant to 2 ug EB/ml . At this concentration cytochromes c and b are present in almost normal or only slightly diminished amounts, whereas cytochromes a + as show an obvious decrease . The mitochondria of the F2 cell show a normal ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Because the same phenomena, that is, generation of megamitochondria with intraorganellar myelin figures and of condensed mitochondria of irregular shape, were also seen in cultured mammalian cells treated with ethidium bromide (King et al, 1972;Klietmann et al, 1973) or chloramphenicol (Smith et al, 1970;King et al, 1972), potent poisons of mitochondrial transcription and translation, respectively, the changes in mitochondrial morphology noticed in the immortalized vim Ϫ fibroblasts may result from reduced rates of macromolecular synthesis as a direct consequence of ROS-induced mtDNA damage. The varying ultrastructural organization of the mitochondria in the different vim Ϫ cell clones presumably reflects alternative ways of adaptation of mitochondrial structure to metabolic requirements continuously changing during the long phase of senescence under the influence of oxidative stress.…”
Section: Mouse Fibroblast Immortalization and Vimentin 699mentioning
confidence: 90%
“…Because the same phenomena, that is, generation of megamitochondria with intraorganellar myelin figures and of condensed mitochondria of irregular shape, were also seen in cultured mammalian cells treated with ethidium bromide (King et al, 1972;Klietmann et al, 1973) or chloramphenicol (Smith et al, 1970;King et al, 1972), potent poisons of mitochondrial transcription and translation, respectively, the changes in mitochondrial morphology noticed in the immortalized vim Ϫ fibroblasts may result from reduced rates of macromolecular synthesis as a direct consequence of ROS-induced mtDNA damage. The varying ultrastructural organization of the mitochondria in the different vim Ϫ cell clones presumably reflects alternative ways of adaptation of mitochondrial structure to metabolic requirements continuously changing during the long phase of senescence under the influence of oxidative stress.…”
Section: Mouse Fibroblast Immortalization and Vimentin 699mentioning
confidence: 90%
“…We found that the cytochrome b 559 is significantly increased by SV40 transformation of cultured cells. Also, in various hepatoma cells such as ascites hepatoma cells and minimal deviation hepatoma cells it increased 13 . It also increases during hepatic carcinogenesis by 3′‐dimethylaminoazo benzene (DAB) in rats.…”
Section: Cytochromes and Production Of Rosmentioning
confidence: 99%
“…Also, in various hepatoma cells such as ascites hepatoma cells and minimal deviation hepatoma cells it increased. 13 It also increases during hepatic carcinogenesis by 3′-dimethylaminoazo benzene (DAB) in rats. They were reported in a series in Cancer Research in 1970-1973.…”
Section: Disturbance Of Complex II Iii and Iv In Mitochondrial Respimentioning
confidence: 99%
“…This technique allowed for the selection of cells which were resistant to chloramphenicol at the level of isolated mitochondrial protein synthesis (8) and whose resistance was a cytoplasmic characteristic (10). Mammalian cells resistant to ethidium bromide have also been reported (11), but the nature of this resistance is not known. Studies of mutants of mitochondrial function are necessary for further elucidation of the nature and function of the mitochondrial genetic system in mammalian cells.…”
mentioning
confidence: 99%